Pemahaman Konsep Struktur Atom Setelah Pembelajaran Menggunakan Model Discovery Learning Berbantuan LKS pada Siswa Kelas X MIA-1 SMA Negeri 1 Paku - Indraniyati Indraniyati; Abdul Hadjranul Fatah; Nopriawan Berkat Asi (FKIP Universitas Palangka Raya, 2020)
The Discovery Learning model is another name for discovery learning. As the name implies, this model directs students to be able to find something through the learning process they live. Students are directed to become accustomed to being scientists. The purpose of this research is to describe the understanding of the concept of atomic structure: the constituent particles of the nucleus, atomic number, mass number, isotope, isotope, and isobar. After learning using the Discovery Learning model assisted by worksheet in Class X Students Public Senior High School 1 Paku, East Barito Academic Year 2017/2018. This study involved 25 students. Data on the results of understanding students' concepts were obtained through the provision of written tests in the form of essays (descriptions) of students before and after using the Discovery Learning model, observation sheets of learning management, student learning activity sheets using rubric of group activity assessment. Data were analyzed using descriptive techniques. The results showed that the majority of students' understanding of the concept had correctly written and explained the atomic symbol as a symbol of elements that was equipped with an atomic number and a mass number of 80%. Describe the understanding of the atomic number (number of protons) as the identity of an element totaling 77.33%. Describe the meaning of mass number as the number of protons and neutrons in an atomic nucleus amounting to 68%. Write down the mass number, the number of protons, the number of neutrons, the number of electrons in the known notation amounting to 69.33%, explaining the meaning of isotopes, isobars, isotons amounting to 74.66%. The average understanding of students' concepts in atomic structure material amounted to 73.86%.